Enhancing EFL Students’ Speaking Confidence through Collaborative Learning - Annida Nur Akfany; Nailul Authar; Edi Pujo Basuki; Mujad Didien Afandi; Novi Rahmania Aquariza (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the role of collaborative learning in enhancing EFL students’ speaking confidence through a qualitative literature review with a systematic approach. The study addresses the issue that many EFL learners experience difficulties in speaking due to affective factors such as anxiety and low self-confidence. Data were collected from academic databases, including Google Scholar, ERIC, and Scopus, focusing on articles published between 2021 and 2026. The selection process followed a structured screening procedure, resulting in a subset of relevant studies for in-depth analysis. The data were analyzed using thematic analysis. The findings indicate that collaborative learning enhances speaking confidence through three interconnected mechanisms: increased social interaction, reduced speaking anxiety, and the creation of a supportive learning environment. However, the effectiveness of this approach may vary depending on contextual factors such as group dynamics and instructional practices. This study suggests that collaborative learning should be implemented with appropriate facilitation to maximize its impact on students’ speaking confidence.